The Implementation of Marketing Mix Strategies and Loyalty Programs in Enhancing Sales and Customer Loyalty at PT Sekar Bengawan - Wirayuda Tamaam Setyo Aji; Arif Hartono (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to gain a comprehensive understanding of the company’s strategy for maintaining customer loyalty, particularly through the implementation of a marketing mix strategy and customer loyalty programs. This internship was conducted to observe how PT Sekar Bengawan, a company in the textile industry, implements marketing mix strategies and customer loyalty programs. To gain this understanding, the author conducted direct observations and collected data from five key informants as part of the data validation process. A qualitative approach was employed in compiling this report, supported by triangulation techniques to ensure the credibility of the data. The analysis consisted of three main stages: data reduction, data presentation, and conclusion. The findings indicate that the implementation of marketing mix elements, namely product, price, place, and promotion, along with customer loyalty initiatives, has contributed positively to enhancing the company’s marketing performance and sustaining long-term customer relationships.